Identification of Prognostic Stromal-Immune Score–Based Genes in Hepatocellular Carcinoma Microenvironment - Liu, Shanshan; Yu, Guangchuang; Liu, Li; Zou, Xuejing; Zhou, Lang; Hu, Erqiang; Song, Yang (Frontiers in Genetics, 2021)
A growing amount of evidence has suggested the clinical importance of stromal and immune cells in the liver cancer microenvironment. However, reliable prognostic signatures based on assessments of stromal and immune components have not been well-established. This study aimed to identify stromal-immune score-based potential prognostic biomarkers for hepatocellular carcinoma (HCC). Stromal and immune scores were estimated from transcriptomic profiles of a liver cancer cohort from The Cancer Genome Atlas (TCGA) using the Estimation of STromal and Immune cells in MAlignant Tumours using Expression data (ESTIMATE) algorithm. Least absolute shrinkage and selection operator (LASSO) algorithm was applied to select prognostic genes. Favorable overall survivals and progression-free interval were found in patients with high stromal score and immune score, and 828 differentially expressed genes (DEGs) were identified. Functional enrichment analysis and protein‐protein interaction networks further showed that these genes mainly participated in immune response, extracellular matrix, and cell adhesion. Matrix metallopeptidase 9 (MMP9) was identified as a prognostic Tumor microenvironment (TME)-associated gene by using LASSO and Tumor IMmune Estimation Resource (TIMER) algorithms and was found to be positively correlated with immunosuppressive molecules and drug response.